Annie Jacobsen’s Phenomena: A Commentary - Marwaha, Sonali (Journal of Scientific Exploration, 2017)
Annie Jacobsen has billed her book Phenomena as a “definitive history of the military’s decades-long investigation into mental powers and phenomena.” The Star Gate program (last of several nicknames) is the ONLY extensive US government sponsored psi program. However, there are far too many errors in Jacobsen’s work to be considered as definitive or even representing the Star Gate program. But first, let me introduce myself. I am Dr. Sonali Bhatt Marwaha, research associate with the Laboratories for Fundamental Research (LFR), Palo Alto, CA. The LFR inherited the psi research begun at SRI, SRI-International (1972-1990), and SAIC (1991-1995), and is actively involved in continuing the research to date. One of our current projects is archiving the Star Gate research from 1972-1995. This is due to be released shortly as: The Star Gate Archives: Reports of the US Govt. Sponsored Psi Program. (1972-1995) (4 Volumes) (McFarland, 2017). As the co-editor of the Star Gate Archives, along with Dr. Edwin C. May, and co-author on several theoretical and experimental papers in this area, I am in a unique position of having reviewed all the US government documents in English, originally released in 2000, on their support and involvement in psi research. I can confidently state that I am the only person so far to have reviewed the complete set of documents released by the CIA, including those in the possession of LFR. This provides me a unique position to comment with authority on Annie Jacobsen’s Phenomena.